2023
DOI: 10.1136/gutjnl-2023-329614
|View full text |Cite
|
Sign up to set email alerts
|

Smart capsules for sensing and sampling the gut: status, challenges and prospects

Muhammad Rehan,
Ibrahim Al-Bahadly,
David G Thomas
et al.

Abstract: Smart capsules are developing at a tremendous pace with a promise to become effective clinical tools for the diagnosis and monitoring of gut health. This field emerged in the early 2000s with a successful translation of an endoscopic capsule from laboratory prototype to a commercially viable clinical device. Recently, this field has accelerated and expanded into various domains beyond imaging, including the measurement of gut physiological parameters such as temperature, pH, pressure and gas sensing, and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…For instance, nanotechnology has been integrated with “smart capsule” technology for the purpose of monitoring intestinal health. 736 These recent advancements and future directions will offer greater convenience for the detection and diagnosis of infectious and inflammatory diseases.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…For instance, nanotechnology has been integrated with “smart capsule” technology for the purpose of monitoring intestinal health. 736 These recent advancements and future directions will offer greater convenience for the detection and diagnosis of infectious and inflammatory diseases.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…This smart pill was a sophisticated programmable capsule that obtained a CE marking. Since then, other projects have emerged as reviewed elsewhere (Rehan et al, [29]). To sample the human microbiome in a noninvasive way and in vivo, Pelican Health has developed an ingestible device that contains no electronics and that has the unique ability to collect three samples at a time.…”
Section: Rationalementioning
confidence: 99%
“…Tang et al have detailed different approaches currently used for sampling the gut microbiome such as endoscopy or biopsy [28]. To date, some research teams have developed non-invasive methods to sense and collect intestinal liquid by using smart capsules [29].…”
Section: Introductionmentioning
confidence: 99%
“… 39–45 We have found that the absence of gut microbiota increases visceral sensitivity to colorectal distention through elevated production of calcitonin gene-related peptide (CGRP) by dorsal root ganglia (DRG) neurons in a sex-dependent manner. 46 Besides the use of gnotobiotic mouse models, the incorporation of modern techniques such as whole genome and targeted metagenomic sequencing, 47 , 48 as well as the use of ingestible sampling devices, 49 , 50 have aided our understanding of gut microbial influence on health and disease.…”
Section: The Gut Microbiomementioning
confidence: 99%